AN EMPERICAL STUDY:IMPACT OF MEDITATION ON QUALITY OF LIFE OF EMPLOYEES OF DELHI (NCR), INDIA - Sheelu Sagar; Vikas Garg; Rohit Rastogi (International Journal of Islamic and Social Sciences (ISOS), 2021)
This is a conceptual and empirical research study with future implications for ‘Wellness Programs' for health promotion and mental well-being for the benefit of the company and its employees. The study's focus is on the concept of training on meditation or mindfulness at work; it will also add to the literature on this topic, which is currently lacking. Meditation can be a valuable business resource for increasing employee productivity, emotional stability, employee well-being, and stress reduction. Young middle-hierarchical engineers (n=30) at PPS International in Greater Noida, Uttar Pradesh, India, were given an eight-week meditation intervention. On the World Health Organization's (WHO) Quality of Life Scale, the experimental group outperformed the control group significantly. The different domains evaluated were perception physical health, psychological health, social relationships, and environment. The WHOQOL-Brief questionnaire responses were summed up in SPSS computational analysis for assessment. There are 26 items on the 5-point Likert scale that were answered before and after the 8-week meditation intervention. After meditation, there was a statistically significant increase in mean differences for Physical Health (t=-21.28, df29, P,0.05), Environment (t=-9.29, df29, P,0.05), Social Relationship (t=-6.84, df29, P,0.05), and Psychological Health (t=-16.33, df29, P,0.05) and Psychological Health (t=-16.33, df29, P,0.05) and Psychological Health.